Estimation Error in Income Determination: A Reply. - Albrecht, William Steve (The Accounting Review, 1978)
Abstract The article presets a reply from William Steve Albrecht on comments made by David E. Keys and Curtis Norton on the topic related to Estimation Error in Income Determination. Certainly, their critique clarifies many of the implicit assumptions and ambiguities in the original paper. The author feels that there are three comments made by Keys and Norton that deserve clarification. They suggest that the author implied the relative frequency interpretation of probabilities that will always be preferable to the subjective interpretation of probabilities in determining forecast error. Since they are essentially the same, the author agreed that a decision about the preferability of one interpretation over the other is a cost-benefit question and is probably situation-specific. Keys and Norton imply that it may have been inappropriate to use a quantification process in the time domain because the underlying process of each time period may not be constant or stable. They also suggested that the level of aggregation of the variances and covariance can affect the magnitude of the confidence interval around net income.